Environmental Impact and Life Cycle Assessment of Economically Optimized Thermal Insulation Materials for Different Climatic Region in Iraq - Saeed Sedeeq, Murad; Kareem Ameen, Shadan; Bolatturk, Ali (International Journal of Engineering and Technology, 2018)
Environmental pollution is one of the biggest problems facing the world, even it is the most dangerous. Therefore, it becomes necessary to combine all efforts to reduce or eliminate it. Iraq is at the forefront of countries that suffer from major environmental problems. The present study aims to perform a comparative environmental assessment for three commonly available thermal insulation materials in Iraq namely expanded polystyrene (EPS), extruded polystyrene (XPS), and rock wool (RW) to select least environmental impact material. A cradle to gate life cycle assessment is performed to assess the environmental impact of each insulation material taking into account manufacturing, transportation, and installation and disposal stages. A life cycle assessment program SimaPro is used to model thermal insulation materials during its life cycle. A life cycle impact analysis method CML 2001 has been selected to assess the environmental aspects associated with two global damage categories as ozone layer depletion and global warming and two regional damage categories as acidification and eutrophication. Economically optimized amount of each insulation material is selected to represent the functional unit of life cycle assessment. The results illustrate that the EPS has the lower contribution in all environmental impact categories for all climatic regions. So, the EPS can be select as a proper thermal insulation material for the building sector from an economic and environmental perspective. The results of LCA are used to determine the amount of CO2 can be reduced per meter square of the exterior wall by using the economical amount of EPS during the lifetime of insulation material. The environmental impact results show that using EPS will contribute in CO2 emission reduction at about 81.5 % in all climatic regions in Iraq.Â